Teach first: what is it doing?. Issue 1 (2nd January 2019) - Spicksley, Kathryn
ABSTRACT: Teach First is a fast-track route to teacher qualification in England and Wales. The initial aim of the programme was to place high-calibre graduates as classroom teachers in schools with challenging social intakes. The programme has grown incrementally since it began in 2002. In 2017, Teach First trained 5 per cent of the total number of postgraduate trainee teachers. Research into Teach First is a growing field but is generally focused on the impact of the programme or the identity of its participants. The aim of this think-piece is not to discuss, or indeed to challenge, the effectiveness of the Teach First programme. Drawing on the theoretical work of Michel Foucault, and in particular his thought on bio-politics, the aim of this article is to open up avenues for critical reflection on the possible effects of Teach First on the wider education and social policy landscape.